The Influence of add-on Service Innovation on Purchasing Decisions At Resorts and Villas in Ubud Mediated by the Behavioral Intention of Multigenerational Family Tourists - Deasy Astrid Natalia; Komang Agus Rudi Indra Laksmana; , I Gusti Ayu Diah Werdhi Srikandi (PT FORMOSA CENDEKIA GLOBAL, 2026)
The hospitality sector faces the intricate challenge of catering to the varied demands of multigenerational family tourists. Innovative ancillary services — or add-ons, encompassing cultural programs, cooking classes, spa packages, children's activities, and private transportation — emerge as a crucial differentiation strategy, significantly boosting perceived value and guest satisfaction. Employing a quantitative, causal research design using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0, the research surveyed 90 multigenerational family tourists selected through purposive sampling. The results reveal that add-on service innovations significantly and positively influence both tourists' behavioral intention (β = 0.517; p = 0.000) and their purchasing decisions (β = 0.297; T = 2.751; p = 0.006). Furthermore, behavioral intention strongly predicts purchasing decisions (β = 0.457; T = 5.380; p = 0.000), and significantly mediates the relationship between add-on innovation and purchasing decisions (p = 0.000; T > 1.96). These findings align with Service-Dominant Logic (SDL) and the Theory of Planned Behavior (TPB), underscoring that strategic add-on innovation drives purchasing decisions both directly and indirectly through the formation of positive behavioral intentions.